PERAN LEMBAGA KESEJAHTERAAN SOSIAL (LKS) DALAM PENANGANAN PENYALAHGUNAAN NAPZA DI JAWA BARAT - Marbun, Jumayar; Aritonang, A.Nelson; Supiadi, Epi; Maryami, Ami; Ismudiyarti, Yuti (Sekolah Tinggi Kesejahteraan Sosial (STKS) Bandung, 2012)
AbstractThe purpose of this study was to obtain an overview of the Institute of Social Welfare (LKS) prevention, rehabilitation, referral, further guidance to victims of drug abuse. While the focus of this study is